2020
DOI: 10.1186/s40733-020-00058-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceived barriers to exercise and their clinical associations in difficult asthma

Abstract: Background: Exercise is recommended in guidelines for asthma management and has beneficial effects on symptom control, inflammation and lung function in patients with sub-optimally controlled asthma. Despite this, physical activity levels in patients with difficult asthma are often impaired. Understanding the barriers to exercise in people with difficult asthma is crucial for increasing their activity, and in implementing successful, disease modifying, and holistic approaches to improve their health. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…However, such finding seemed to be inconsistent with a prior study that examined the association between BMI, exercise, and lung function among asthmatic adolescents and reported no association between PA capacity and FEV 1 for those with obesity 38 . The reasons for this discrepancy may be that FEV 1 and asthma control are two different indicators and seem to have discordant association with PA as reported in previous studies 39,40 . Additionally, exercise capacity is a reflection of maximal oxygen consumption and physical limitation, 41 while PA level represented lifestyle inclination.…”
Section: Discussionmentioning
confidence: 76%
“…However, such finding seemed to be inconsistent with a prior study that examined the association between BMI, exercise, and lung function among asthmatic adolescents and reported no association between PA capacity and FEV 1 for those with obesity 38 . The reasons for this discrepancy may be that FEV 1 and asthma control are two different indicators and seem to have discordant association with PA as reported in previous studies 39,40 . Additionally, exercise capacity is a reflection of maximal oxygen consumption and physical limitation, 41 while PA level represented lifestyle inclination.…”
Section: Discussionmentioning
confidence: 76%
“…The stability of body mass index provides some reassurance that these changes are not merely a result of reduced adiposity-driven inflammation. Demonstration of the disease-modifying benefits of exercise in asthma should go a long way in increasing uptake in patients with greater perceived barriers to activity [ 46 ]. There is support for our findings from work in other chronic inflammatory diseases, summarised in a review that suggests exercise interventions exert antioxidant effects [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, asthmatic patients are often afraid to engage in physical activity. Analysis of psychological barriers that interfered with active lifestyles in patients with asthma showed that a high level of psychological barriers was significantly correlated with increased asthma symptoms, anxiety and depression, low quality of life and amount of oral glucocorticosteroids used in the last 12 months [17]. Asthmatic patients are especially avoidant when it comes to a vigorous activity as it is associated with exercise-induced bronchoconstriction [18].…”
Section: Discussionmentioning
confidence: 99%